A Comparison of Acute Neurocognitive and Psychotomimetic Effects of a Synthetic Cannabinoid and Natural Cannabis at Psychotropic Dose Equivalence - Theunissen, Eef Lien; Kuypers, Kim Paula Colette; Mason, Natasha Leigh; Ramaekers, Johannes Gerardus (Frontiers in Psychiatry, 2022)
Due to differences in potency, efficacy, and affinity for CB1 receptors, it is challenging to compare the effects of natural cannabis and synthetic cannabinoids (SCs) at equipotent doses. Therefore, the current study compared the effects of natural cannabis (THC) and an SC, JWH-018, at psychotropic dose equivalence. Participants from two previous placebo-controlled studies were matched for their levels of subjective high, to compare neurocognitive and psychotomimetic effects of THC and JWH-018. At equal subjective intoxication levels, both drugs impaired psychomotor, divided attention, and impulsivity performance, with no significant difference between the two drugs. Both drugs also caused significant psychotomimetic effects, but dissociative effects were considerably more pronounced for JWH-018 than THC. We conclude that psychotropic dose equivalence provides a uniform approach for comparing the neurocognitive and psychotomimetic profiles of CB1 agonists, which can also be applied to other drug classes.